A infraestrutura logística e a consolidação do modelo exportador de base primária brasileira - Alves, Phábia Valeska Vale (2016)
Currently much has been said about logistics infrastructure in order to promote and support industrialization in the country and many levels of government have been implemented to promote regional and national macrologísticos equipment, however, that in fact such investments provided were effects for stimulus industrialization. This study aims to show whether the infrastructure investments will contribute to the development of an industrial sector, or whether it will contribute to the export sector of primary goods. Therefore, it made use of a literature search, which provides the theoretical basis for the development of this thesis, comparing work on the theory of neo-developmentism, analyzing existing literature on infrastructure in Brazil, an analysis of the industrial sector, is doing secondary data collected on exports and imports of primary commodities and manufactured goods, as a statement on de-industrialization in the country. It is observed in this work, the opposite effect industrialization, comes from a neoliberal policy (even with a leftist said government in the country), who preaches the non-interventionism of the state in the economy, is also observed that the poor performance achieved in recent years in the Brazilian industry is precisely due to the absence of Industrial policy Interventional, which the Neodesenvolvimentistas is necessary because the great economic powers of today's world have developed the basis of protectionist economic policies. Seeks to show, therefore, that the Investment in Infrastructure Logistics, analyzed from government programs such as the PAC (Growth Acceleration Program) and PNLT (National Plan of Logistics and Transport) are not the solution to promote industrialization in the country, but which end up contributing to consolidate an export model based on commodities and / or low technological intensity.